Antidiabetic Effects Of Robusta Coffee Bean Ethanol Extract (Coffea Canephora) In Diabetic Mice With Alloxan Induction - Wulandari, Ayu; Hidayati, Sholihatil; Dina Trianggaluh Fauziah (Sean Institute, 2024)
Non-communicable diseases are a group of diseases which in themselves become a public health burden because they are widespread, one of which is diabetes mellitus (DM). Robusta coffee bean (Coffea canephora) is one of the medicinal plants that can be efficacious in lowering blood glucose levels. The purpose of this study was to determine the effect of Robusta Coffee Beans (Coffea canephora) on blood glucose levels in alloxan-induced mice. This study used a type of laboratory experimental study using male mice (Muss musculus L.) Bulb/C strain. There were 6 groups randomized and treated Robusta Coffee Bean Ethanol Extract (RBEE) with dose 100 mg/kg.bw, dose 200 mg/kg.bw, dose 400 mg/kg.bw, CMC Na 0.5% and metformin 195 mg/kg.bw. The treatment is given orally for 14 days. Blood glucose level data was analyzed using the ANOVA one-way parametric test with a confidence level of 95%. After being given treatment, the blood glucose level in negative control group (545.7 mg/dl), positive control (130.25 mg/dl), RBEE 100 mg/kg.bw (296.5 mg/dl), RBEE 200 mg/kg.bw (211.5 mg/dl), RBEE 400 mg/kg.bw (147.25 mg/dl), so that the percent decrease in blood glucose levels in RBEE 100 mg/kg.bw (27.10%), RBEE 200 mg/kg.bw (50.14%), RBEE 400 mg/kg.bw (68.00%), CMC Na (-53.60%), metformin (71.11%). The results showed that there was an effect on reducing blood glucose levels in mice significantly compared to the negative control group. Robusta coffee beans (Coffea canephora) have the activity of lowering blood glucose levels so that it can be developed as an antidiabetic.